Greenovation: Literasi Transformasi Sampah Menuju Karakter Unggul dalam Perspektif Ekonomi, Pendidikan dan Teknologi - Putri, Meirin Dwiningtyas; Fazriansyah, Muh Fajar; Sirri, Evi Latifatus; Saputra, Muhammad Akmal; Hermawanti, Ajeng Novia (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Waste management is one of the efforts to reduce the impact of environmental damage. The existence of counseling or socialization and training on household waste management in the community of Puspamukti Village, Cigalontang District, Tasikmalaya Regency is expected to understand the importance of household waste management in an environmentally friendly way, namely by sorting organic and inorganic waste and applying the 3R principle (reuse, reduce and recycle). In addition, the community received training in worm cultivation using the utilization of cultivation media derived from organic waste and worm feed nutrition from organic waste as well as making valuable products.